2014
DOI: 10.1186/s40478-014-0080-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrogyria: pathology, fetal origins and mechanisms

Abstract: Polymicrogyria (PMG) is a complex cortical malformation which has so far defied any mechanistic or genetic explanation. Adopting a broad definition of an abnormally folded or festooned cerebral cortical neuronal ribbon, this review addresses the literature on PMG and the mechanisms of its development, as derived from the neuropathological study of many cases of human PMG, a large proportion in fetal life. This reveals the several processes which appear to be involved in the early stages of formation of polymic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 94 publications
1
36
0
Order By: Relevance
“…Polymicrogyria (shown in Figure 1g) is a complex congenital malformation where the surface of the fetal brain normally has many ridges or folds, called gyri [23]. Friede et al [24] defined polymicrogyria as “an abnormally thick cortex formed by the piling upon each other of many small gyri with a fused surface”.…”
Section: Introductionmentioning
confidence: 99%
“…Polymicrogyria (shown in Figure 1g) is a complex congenital malformation where the surface of the fetal brain normally has many ridges or folds, called gyri [23]. Friede et al [24] defined polymicrogyria as “an abnormally thick cortex formed by the piling upon each other of many small gyri with a fused surface”.…”
Section: Introductionmentioning
confidence: 99%
“…The migration defect in KBP knockdown brains may be correlated to the PMG phenotype, characterized by numerous small, unfolded gyri, and disorganized lamination, in GOSHS patients (Valence et al, 2013; Squier and Jansen, 2014; Kato, 2015). Previous studies have shown that defects in neuronal migration caused MCDs, including lissencephaly and PMG (Tsai et al, 2005, 2007, 2016; Vallee and Tsai, 2006; Vallee et al, 2009; Jheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of AFs or cortical infoldings in PMG remains to be unknown. Some researchers have suggested that there is a failure in the attachment of glial radial fibers to the pial limiting membrane and gaps are formed in the membrane [15][16][17] . PMG is postulated to occur as a result of incomplete migration and accumulation of neuronal cells to form dysmorphic cortical layers and small gyri close to the germinal matrix.…”
Section: Discussionmentioning
confidence: 99%